A comment on "Translation and scale invariants of Tchebichef moments" by Hongqing Zhu [Pattern Recognition 40 (2007) 2530–2542]. (May 2018) - Wang, Xuan; Shi, Guanghui; Guo, Fangxia
Highlights: It points out wrong claim made by (Hongqing Zhu, 2007). It corrects this error by developing and using Charlier moment. The proposed Charlier moment is a novel category. Abstract: The aim of the present comment is to point out wrong claim made by (Hongqing Zhu, 2007) on the computation of scaling invariants of Tchebichef moments. We also proposed a novel discrete orthogonal moments namely Charlier moments, and demonstrate that the scaling invariants of the Charlier moments can be computed by using the method mentioned in the article of (Hongqing Zhu, 2007). Experimental results show that our inference is correct.